Study protocol: a pragmatic randomised controlled trial of a 12-week physical activity and nutritional education program for overweight Aboriginal and Torres Strait Islander women - Canuto, Karla J (BioMed Central, 2011)
BACKGROUND: Aboriginal and Torres Strait Islander women have a higher prevalence and incidence of obesity and type 2 diabetes than non-Indigenous Australian women. Physical inactivity is a key modifiable risk factor for obesity and evidence shows that even modest reductions in waist circumference (WC) have significant health benefits. Trialing physical activity programs in difficult-to-reach high risk groups, especially urban Indigenous Australians poses distinct implementation challenges. METHODS/DESIGN: The trial objective is to evaluate the effectiveness of a structured 12-week physical activity group program with nutritional advice. The design is a pragmatic randomised controlled trial. This study protocol describes the implementation and evaluation of the program. Participants are randomised into either an intervention or waitlisted group. The waitlisted group have a 12 month waiting period before commencing the 12-week program. Participant data is collected at baseline, 12, 24 and 52 weeks. Participants are Aboriginal and Torres Strait Islander women, aged 18-64 years with a waist circumference greater than 80 centimetres residing in Adelaide. The primary outcome measure is WC change immediately post program from baseline. Secondary outcomes include short term and long term changes in WC, weight, blood pressure, fasting blood glucose, insulin, insulin resistance (calculated HOMA), haemoglobin A1C (HbA1C), triglycerides and C-reactive protein (CRP). Behavioural and psychosocial surveys are administered to assess physical activity, dietary intake and the participant's motivation, self-efficacy and perceived social support for physical activity. Qualitative interviews focusing on participants' motivation, enablers and barriers to healthy eating and physical activity will be undertaken. Implementation fidelity and participation are also assessed. DISCUSSION: The Aboriginal and Torres Strait Islander Women's Fitness Program (WFP) is designed to provide a rigorous physiological and client-based evaluation of a structured 12-week program aimed to increase metabolic fitness and reduce WC in this high risk population. Evaluation results aim to provide the support necessary to design programs that are accessible, affordable and effective at reducing WC, while also improving the metabolic profile of overweight Aboriginal and Torres Strait Islander women. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12610000224022